ACTR-48. FEASIBILITY OF DISCONTINUATION OF ADJUVANT TEMOZOLOMIDE AFTER 12 CYCLES REMAINING WITHOUT PROGRESSION FOR PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA. (5th November 2018) - Nagane, Motoo; Kobayashi, Keiichi; Saito, Kuniaki; Shimizu, Saki; Suematsu, Shinya; Kume, Satoshi; Okamura, Yuma; Shiokawa, Yoshiaki
Abstract: BACKGROUND: Standard of care for newly diagnosed glioblastoma (GBM) has been chemoradiotherapy with concomitant and adjuvant temozolomide (TMZ) (Stupp regimen). Optimal number of adjuvant TMZ cycles, however, has not been well established yet, although the pivotal trial used 6 cycles. In routine practice, up to 24 cycles have been frequently given, while many recent trials have adopted 12 cycles without solid evidence. Here we investigated outcome of and prognostic factors associated with discontinuation of adjuvant TMZ after 12 cycles without progression. METHODS: Ninety six patients treated with Stupp regimen since May 2007 to March 2017 in our institution were retrospectively analyzed. Overall survival (OS) and progression-free survival (PFS) were evaluated with Kaplan-Meier method and statistical significance was determined by logrank test. RESULTS: There were 20 patients (21%, med age 57 yo; med KPS 70; female 12) identified who completed 12 adjuvant TMZ cycles without progression. Nine patients discontinued adjuvant TMZ (Group A), while 11 continued beyond 12 cycles (Group B). Median PFS (mPFS) and median OS (mOS) were 40.6 m and 53.7 m, respectively. mPFS after 12 cycles of adjuvant TMZ (mPFS-TMZ12) for all 20 patients, Group A, and B were 26.8 m, 96.2 m, and 26.8 m (p=0.379 for latter 2), respectively. mOS after 12 cycles of adjuvant TMZ (mOS-TMZ12) were 40 m, not reached, and 27.2 m (p=0.080), respectively. Factors significantly associated with better PFS were young age, female, higher KPS, debulking resection, and no residual enhancing disease (NRD) at TMZ12, and were female, debulking resection, and NRD at TMZ12 with OS. CONCLUSIONS: A minor subset of GBM patients could continue adjuvant TMZ for 12 cycles without progression and benefited for better survival. In this cohort of patients, discontinuation of adjuvant TMZ after 12 cycles may not compromise their outcome, especially in those with no residual disease.